LYMPH-V: A wearable arm volume measurement device and mobile application for the prevention and early detection of breast cancer-related lymphedema: A study protocol - İsmail Toygar; Gülcan Bağçivan; Ayşe Arıkan Dönmez; Furkan Bilek; Çiğdem Fulya Dönmez; Pınar Borman; Mehmet Durmuş Çalışır; Yasin Karan; Elif Deniz Kaçmaz (Nursing Practice Today, 2025)
Background & Aim: Early detection of lymphedema is crucial to prevent progression to advanced stages that impair the quality of life in breast cancer survivors. This study aims to develop and evaluate LYMPH-V, a wearable arm volume measurement device and mobile application designed for the prevention and early detection of breast cancer-related lymphedema. Methods & Materials: The study consists of two phases. In the first phase, the LYMPH-V wearable device and a supportive mobile application will be developed. The app will feature five core components: exercise modules, educational content, coping strategies, arm volume measurement/recording, and personalized reminders. Content will be created based on current guidelines and expert opinions. In the second phase, the effectiveness of the intervention will be assessed through a pilot randomized controlled trial, a reproducibility study, and usability evaluations. The device uses stretch sensors to monitor arm volume, and the mobile app provides alerts if measurements suggest early signs of lymphedema. Data will be stored securely and shared with healthcare professionals upon user approval. Results: Expected outcomes include high usability, strong agreement with manual measurements, and improved capacity for at-home lymphedema monitoring and prevention. Conclusion: LYMPH-V offers a promising digital solution that empowers survivors and healthcare providers through home-based arm volume tracking. This approach may facilitate early intervention, reduce healthcare burden, and enhance quality of life for breast cancer survivors.